Photoredox-mediated aminoalkylation and carbamoylation of azomethine imines - Matsuo, BiancaTaeko (2021)
Over the past decade, the organic synthetic community has witnessed the emergence of a new and complementary approach to the conventional radical chemistry. Photochemistry has proven to be a powerful and more sustainable tool through the photoredox catalysis concepts, which are based on the use of organic and metallic photocatalysts capable of absorbing visible light irradiation and converting it into electrochemical potential, promoting the rationalization of new disconnections that are not viable or difficult to be achieved by conventional methods. Nitrogen-centered 1,3-dipoles are considered key building blocks for the preparation of five-membered heterocyclic compounds and are widely explored in (3 + 2) cycloaddition reactions. Despite the advances in translating these reactions under photocatalytic conditions, the use of such dipoles - except for nitrones and azides - remains scarcely explored. Among this class of versatile compounds, azomethine imines presents a zwitterionic nature that have been mainly explored in 1,3-dipolar cycloadditions and only few reports involving photoisomerization and photocyclization promoted by ultraviolet irradiation were disclosed in the literature. In this scenario, we initially became interested in exploring the reactivity of azomethine imines under visible-light irradiation. To this end, we envisioned that the easily generated and reactive α-aminoalkyl radicals would be ideal coupling partners for the development of a new photoredox functionalization strategy of azomethine ions leading to the synthesis of N-(β-aminoalkyl) pyrazolidinones under mild reaction conditions. Having proven the reactive potential of these species under the photoredox catalysis, we then challenged them in a one-electron approach for amide bond installation in the presence of readily available and stable 4-carbamoyl-1,4-dihydropyridines as carbamoyl radical source. The principal relevance of the developed protocol relies on the rich nature of the accessed compounds, as a library of diversified amino acid derivatives, including more complex substrates and drug derivatives. We demonstrated that photoredox catalysis is an excellent strategy for the a-functionalization of azomethine imines, leading to an easy access to high functionalized compounds through a new a-amino functionalization protocol and by installing amide bonds. The potential of the developed methods was demonstrated preparing complex examples involving peptides, pharmaceutical ingredients, and sterically hindered amides.